Analysis and nursing countermeasures of knotted intravascular catheter in a patient with invasive arterial pressure monitoring (有创动脉血压监测中穿刺导管血管内打结1例分析与对策) - YU Mengjia (于梦佳); LIU Qiong (刘琼); HU Suqin (胡素勤); HUANG Zaiyu (黄宰宇); ZHANG Lei (张磊) (中西医结合护理)
This paper analyzed factors of knotted intravascular catheter in a patient with invasive arterial pressure monitoring, summarized countermeasures for removal of knotted intravascular catheter, and provided reference for improvement of safe catheter placement. (本文分析1例有创动脉血压监测中穿刺导管血管内打结的原因, 总结相应对策, 为提高置管安全性提供参考意见。)